Kerjasama Malaysia dan ASEAN dalam Menghadapi Pandemi COVID-19 di Kawasan Asia Tenggara Tahun 2020 - Ushwatul Jannah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The Covid-19 outbreak, which is still being felt by all levels of society in the world, is increasingly leaving a major impact so that countries are overwhelmed with prevention and anticipation. Malaysia as one of the ASEAN member countries is no exception feeling the impact of the rapid spread of the Covid-19 virus. The purpose of this study is to explain how Malaysia and ASEAN collaborate in dealing with the COVID-19 pandemic in the Southeast Asia region in 2020. Furthermore, this paper will use a research method with a qualitative approach that is used to explore and understand the meaning of a number of individuals and groups who ascribed to social and humanitarian problems. Based on this qualitative approach, the author will study further about Malaysia's membership and relations with ASEAN, then proceed to a discussion on the development of the 2020 COVID-19 pandemic in Malaysia. The next discussion examines how ASEAN's response to the COVID-19 pandemic in the Southeast Asian region, which is continued by discussing how Malaysia's participation in handling COVID-19 in ASEAN. And ended with a discussion about the projected opportunities and challenges of Malaysia and ASEAN related to efforts to deal with COVID-19 in the Southeast Asian region. The discussion will refer to four mechanisms for handling COVID-19 based on the ASEAN-ASCC pillars, namely: The ASEAN Health Ministers and ASEAN Plus Three Health Ministers and the ASEAN Plus Three Senior Officials Meeting for Health Development (APT SOMHD), The ASEAN Emergency Operations Center. Network for public health emergencies (ASEAN EOC Network), and the ASEAN Bio Diaspora Virtual Center for big data analytics and visualization (ABVC).